P202 Developing a database with sensitive health information: a profile of people living with HIV in newfoundland and labrador. (14th July 2019) - Asghari, Shabnam; Boyd, Sarah; Blackmore, Jillian; Hurley, Oliver; Knight, John; Kelly, Deborah; Burt, Kimberly; Pittman, Beatrice; Gilbert, Laura; Dowden, Jeff
Abstract : Background: In Newfoundland and Labrador (NL), people living with HIV (PLHIV) primarily receive care through an interdisciplinary HIV specialty clinic, however, HIV care has been transitioning to primary healthcare elsewhere. Developing a comprehensive cohort of PLHIV to help improve healthcare has long been the vision of researchers, clinicians and decision makers. The objective of this study was to develop a de-identified cohort of PLHIV in NL, to be used to inform policy and prioritize healthcare system changes to optimize HIV healthcare in NL and to address gaps in care for PLHIV. Methods: Data was collected from a number of different databases and PLHIV were identified as having HIV from three sources: 1. NL Public Health Laboratory data; 2. HIV Clinic data; 3. Medical Administration data. Results: The finalized dataset included 317 people who had been diagnosed with HIV in NL as of 1994 and 251 were still alive at the end of data collection. The final database contained a total of 178 variables describing PLHIV health and health care utilization. Only 7% of PLHIV were identified by all three sources suggesting no single provincial HIV data custodian captures all those living with HIV in the province. Conclusion: It is important that policy be implemented to merge siloed data sources in order to provide researchers, clinicians and decision makers with the accurate and complete data that is required to conduct sound and precise research, provide appropriate care and allocate resources to health initiatives that can improve the quality of life for PLHIV. Disclosure: No significant relationships.